La professionnalisation des moniteurs d’atelier en Établissement et Service d’Aide par le Travail (ESAT) : un éclairage par la recherche-intervention - Dominique Broussal; Jean-François Marcel; Lucie Aussel (Éducation et Socialisation)
This article is interested in the field of the professionalization of the workshop's instructors, who exercise in establishment of help service by the work (ESAT). The professionalization is approached under the angle of the processes of structuring and reinvention of their trade. Because of numerous evolutions, this trade is indeed in transfer, taken between sometimes rival logics : the one centered on the accompaniment of the handicaped worker, the other one centered on the production. The methodology consists of the analysis of twelve educational fact sheets co-developed by 12 instructors, 2 psychologists and 3 researchers, during an intervention-research. The analysis highlights the main characteristics of the processes of structuring and reinvention as well as the importance held by the political logic, polarized by the institution and consisting in producing arbitrations in terms of piloting, strategies and organization of the work.